Empirical analysis on impact of FDI on the level of urbanization in costal areas - Can-Ming Cao; Jin-Jun Duan (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: There is a close relationship between FDI and the level of urbanization. the objective of this research is to analyze the relationship between FDI and the level of urbanization in Jiangsu and Guangdong provinces in costal areas. Design/methodology/approach: The author uses the modern econometric methods by panel unit root test, cointegration test, random effects models and fixed effects models, and the data of FDI (2000-2012), urbanization rate, industrial structure and regional GDP of Nanjing, Xuzhou, Suzhou, Wuxi and other 13 cities in Jiangsu Province, Guangzhou, Shenzhen and other 19 cities in Guangdong province, researches the relationship between FDI and urbanization rate. Findings: Models show, FDI was closely correlated with urbanization rate in Jiangsu province and Guangdong province, the highly correlated with industrial structure, while it negatively correlated with the growth of GDP, and the degree of correlation is not high in Jiangsu province, but the high negative correlation in Guangdong province. The results shows the industrial structure and the urbanization rate mainly cause FDI growth. Research limitations/implications: There are many provinces in costal areas of China, this paper just research the relationship between FDI and the level of urbanization in Jiangsu province and Guangdong province, there are some limitations in the study areas and results. Originality/value: The study was the first to successfully apply on random effects model and fixed effects model to study the relationship between FDI and the level of urbanization in coastal areas by competitive analysis. Guangdong and Jiangsu province are the most developed regions, they are the most representative provinces in costal areas of China. Taking these two province as an example, we can analyze the relationship between FDI and the level of urbanization in central and western regions.
Keywords: 650; urbanization; FDI; urbanization rate; industrial structure; costal areas